TRANSLANGUAGING CONCEPT AND FUNCTION PERFORMED IN ‘HALUSTIK’ FILM AS A LINGUISTIC RESOURCE FOR INDONESIAN ENGLISH LEARNERS - Nur Ekaningsih (Universitas Muria Kudus, 2020)
The language phenomenon which is often called Translanguaging is an activity and process of language shifting. It includes the transformation between languages that are used with various other language sources to improve certain language skills. This research raised a romantic drama consisting of 13 episodes with several famous stars in Indonesia. Through data from the drama film of HALUSTIK, the researcher described the concept, function, benefits and linguistic resources that could be learned from translanguaging in this drama film. The language used in this film was dominated by 45% Indonesian, 40% English, 20% Sundanese and Javanese. The findings in this study, the researcher described the category of translanguaging in a concept that was divided into two, namely translanguaging space and translanguaging instinct. Whereas translanguaging functions were explained based on the communication carried out in the drama of HALUSTIK film taken from the first episode to the third. In addition, the benefits after watching this film, English learners in Indonesia could get some useful English expressions, fluent English pronunciation that could be transformed into Indonesian in a smooth and creative manner. The use of the Indonesian language that supported English in this film was very helpful to improve the source of knowledge and was able to provide a better understanding. The conclusion that can be taken after analyzing the Halustik drama film is that translanguaging does not damage the original language, it even supports understanding to facilitate the use of other languages. In this film, Indonesia language supports other language, namely English. Keywords: translanguaging; concepts; functions; linguistic resource